A case of psoas cold abscess in a young tuberculosis patient - Ikeda, T (Hinyokika kiyo. Acta urologica Japonica, 2000)
A 28-year-old man was referred to our hospital with a complaint of painful induration of right epididymis accompanied with right back pain and persistent low-grade fever. He was finally diagnosed with tuberculosis by sputum culture. Abdominal computed tomography (CT) revealed right psoas abscess and vertebral caries. He underwent a percutaneous drainage of the abscess followed by multidrug (streptomycin, pyrazinamide, refanpicin, isoniazide) combination therapy. Immediately after the drainage, symptoms began to improve with these therapies. However, four months later, abdominal CT showed a worsening of the abscess. Recently there is a stagnation in the decline of incidence of tuberculosis. It is still necessary to examine young people carefully bearing urogenital tuberculosis in mind. The pathogenesis and management of this rare condition are discussed